Sideways stories from Wayside School - Sachar, Louis, 1954-; Brinckloe, Julie (New York : Avon Books, 1985)
Presents humorous episodes from the classroom on the thirtieth floor of Wayside School, which was accidentally built sideways with one classroom on each story.
3.9
3-6
3-6
Elem. School Library Collection
Book Links (A.L.A.)
Kliatt
Keywords: Schools -- Fiction; Humorous stories; School stories; Humorous fiction